Quantity and spatial imbalance of supply and demand for water yield services in terrestrial ecosystems under different future land use scenarios in Xinjiang, China - Liu, Zhuo; Shi, Mingjie; Wu, Hongqi; Jiang, Pingan; Zhang, Haoyu; He, Panxing; Zheng, Kai; Dong, Tong; Zhang, Yue (Frontiers in Ecology and Evolution, 2023)
Drylands in northwest China have limited water resources, which negatively impacts economic development, ecological security, and the United Nations Sustainable Development Goals. However, few studies have examined water supply and demand under multiple future spatial patterns of land use, particularly under different sustainable development scenarios. Further research is therefore needed to determine how water supply and demand will affect water output services under various land use patterns. We used the GMOP-PLUS (Gray Multi-objective Optimization-Patch-generating Land Use Simulation) and the InVEST (Integrated Valuation of Ecosystem Services and Tradeoffs) models to investigate future land use programs and the current and future trends in water yield services supply and demand in the typical dryland region of Xinjiang, China. The GMOP-PLUS model was used to project the spatial patterns of land use/land cover (LULC) change in Xinjiang in 2025 and 2030 under programs of natural development, rapid economic development, ecological land conservation and sustainable development. We then used the InVEST model to project the spatiotemporal evolution of water yield services supply and demand under the four different scenarios. Our results show that under the four scenarios for 2025 and 2030, the quantity and spatial distribution of water production in Xinjiang is unbalanced, with both water supply and demand increasing over time, but with demand always greater than supply. The supply of, and demand for, water yield services under the ecological land protection and sustainable development scenarios were close to equilibrium, but water resources were still scarce. Programs for advancing sustainable development narrow the supply–demand gap for services that produce water. This study has significant implications for future land use planning and conservation of ecosystem water production services in the study area.